Respuesta :

Answer:

yes

Step-by-step explanation:

3x5=15

3x1=3   15+3=18

7x5=35

7x2=14   35-14=21    21-3=18

18=18

Proof:

Given [tex]3(x+1)=7(x-2)-3[/tex]

To prove that the solution of  [tex]3(x+1)=7(x-2)-3 [/tex] is 5,

[tex]3(x+1)=7(x-2)-3[/tex]

On taking off the brackets we get,

[tex]3x+3=7x-14-3[/tex]

On grouping the x terms together,

[tex]7x-3x=14+3+3[/tex]

On solving we get,

[tex]4x=20[/tex]

[tex]x=\frac{20}{4}[/tex]

On dividing 20 by 4,

[tex]x=5[/tex]  

[tex]\Rightarrow[/tex] Hence proved that the solution for [tex]\bold3(x+1)=7(x-2)-3\bold[/tex] is 5.